Legal Protection of Investors in Initial Public Offering Against Liquidity Exit Practices - MUHAMMAD INDRA MUHTAR; ANDRY SETIAWAN (Law Research Review Quarterly, 2026)
This study aims to analyze the legal protection for retail investors against the practice of liquidity exit carried out by controlling shareholders in the Initial Public Offering mechanism in Indonesia. The phenomenon of exit liquidity shows a shift in the function of IPO from business expansion to a means of transferring business risk from the old owner to the public, which often causes significant losses for retail investors due to information asymmetry and massive stock sales after the IPO. This study uses a normative juridical research method, although the current capital market regulations have provided procedural certainty, there is still a legal vacuum in limiting the volume of divestment of controlling shares after the IPO. This condition is exacerbated by the exchange's technical policies such as the closing of the broker's code on the JATS system in real time which hinders trading transparency. This study recommends the need for regulatory reform through the adoption of quantitative restrictions on the volume of stock sales as per the standard of SEC Rule 144 in the United States or UAE Federal Decree Law no. 32 of 2021 on Commercial Companies as well as the acceleration of the demutualization of the Indonesia Stock Exchange to ensure the integrity of the capital market.